Determination of Caffeine Content in Ethanolic Extract of Robusta Coffee Beans (Coffea canephora) Using UV-Vis Spectrophotometry - Vina Purnamasari; Ririn; A Hasrawati (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Caffeine is one of the main bioactive compounds in robusta coffee beans (Coffea canephora) that has potential applications in pharmaceutical and cosmetic formulations, particularly for hair growth stimulation. This study aimed to determine the caffeine content in ethanolic extract of robusta coffee beans using UV-Visible spectrophotometry. The research was conducted using an experimental laboratory design. Robusta coffee bean extract was obtained by maceration using ethanol as the solvent. Qualitative identification of caffeine was followed by quantitative analysis using UV-Vis spectrophotometry at a maximum wavelength of 273 nm. A calibration curve was constructed using standard caffeine solutions, and the caffeine content of the extract was calculated based on the linear regression equation. The results showed that the calibration curve exhibited good linearity within the tested concentration range. Quantitative analysis revealed that the caffeine content of the ethanolic extract of robusta coffee beans was 221.58 mg/g extract, which is consistent with previously reported caffeine levels in Coffea canephora. These findings confirm that robusta coffee beans are a significant natural source of caffeine and support their potential utilization as raw material for pharmaceutical and cosmetic products. This study provides quantitative data that may serve as a scientific basis for further formulation development and quality control of caffeine-containing herbal products.